Madrasah Principals as Academic Supervisors: Advancing Teacher Professionalism Through Merdeka Curriculum Implementation at State Madrasah Aliyah - Muhammad Amin; Abdullah Idi; Saipul Annur (STAI Hubbulwathan Duri, 2025)
The role of the madrasah principal as an academic supervisor is crucial in implementing the Merdeka Curriculum and fostering teacher professionalism. This study explores the management strategies of the madrasah principal at MAN 1 Prabumulih City in developing teacher competence within this curriculum framework. A qualitative case study approach was employed, utilizing in-depth interviews, direct observation, and document analysis to gather data. This method provided a comprehensive understanding of the principal’s supervisory role and its impact on teacher development. Findings indicate that the principal plays a vital role as a motivator and facilitator, supporting teachers through both pre-service and in-service training programs. An inclusive and collaborative approach fosters a dynamic learning environment, with active teacher and student participation as key success indicators. However, challenges such as teacher readiness and scheduling constraints remain. Despite these challenges, effective supervision, continuous training, and strategic time management are essential in overcoming barriers to teacher professionalism. The study highlights the importance of leadership in ensuring successful curriculum implementation. Madrasah principals play a pivotal role in enhancing teacher professionalism through active supervision and training strategies. Continuous professional development efforts, including structured mentoring programs, are essential for improving teacher competence. This research contributes to the discourse on educational leadership and provides practical insights for madrasah principals on effective supervision in curriculum implementation.